137k views
2 votes
Subtract (-9x^2+8x-14) from the sum of (-9x^2-10x) and (3x^2+3x+7)​

User Weekend
by
5.5k points

1 Answer

7 votes

Answer:


3x^2 - 15x + 21\\or\,\,3(x^2 -5x +7)

Explanation:

First we will find sum of
(-9x^2-10x)\,\, and\,\, (3x^2+3x+7)

Adding the like terms:


= -9x^2-10x + 3x^2 +3x+7\\= -9x^2+ 3x^2 -10x+3x+7\\= -6x^2 - 7x +7

Now subtract (-9x^2+8x-14) from (-6x^2 - 7x +7)


=(-6x^2 - 7x +7) - (-9x^2+8x-14)\\= -6x^2 - 7x +7 +9x^2-8x+14\\= -6x^2 +9x^2 - 7x -8x+7 +14\\= 3x^2 - 15x + 21\\=3(x^2 -5x +7)

User Jens Kohl
by
5.6k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.